The Efficacy of Wrestling-Style Compression Suits to Improve Maximum Isometric Force and Movement Velocity in Well-Trained Male Rugby Athletes - McMaster, Daniel T.; Beaven, Christopher M.; Mayo, Brad; Gill, Nicholas; Hébert-Losier, Kim (Frontiers in Physiology, 2017)
PURPOSE: The prevalence of compression garment (CG) use is increasing with athletes striving to take advantage of the purported benefits to recovery and performance. Here, we investigated the effect of CG on muscle force and movement velocity performance in athletes. METHODS: Ten well-trained male rugby athletes wore a wrestling-style CG suit applying 13-31 mmHg of compressive pressure during a training circuit in a repeated-measures crossover design. Force and velocity data were collected during a 5-s isometric mid-thigh pull (IMTP) and repeated countermovement jump (CMJ), respectively; and time to complete a 5-m horizontal loaded sled push was also measured. RESULTS: IMTP peak force was enhanced in the CG condition by 139 ±142 N, (effect size [ES] = 0.36). Differences in CMJ peak velocity (ES = 0.08) and loaded sled-push sprint time between the conditions were trivial (ES = -0.01). A qualitative assessment of the effects of CG wear suggested that the likelihood of harm was unlikely in the CMJ and sled push, while a beneficial effect in the CMJ was possible, but not likely. Half of the athletes perceived a functional benefit in the IMTP and CMJ exercises. CONCLUSION: Consistent with other literature, there was no substantial effect of wearing a CG suit on CMJ and sprint performance. The improvement in peak force generation capability in an IMTP may be of benefit to rugby athletes involved in scrummaging or lineout lifting. The mechanism behind the improved force transmission is unclear, but may involve alterations in neuromuscular recruitment and proprioceptive feedback.